PENGHENTIAN PENYELIDIKAN BERDASARKAN RESTORATIVE JUSTICE MENURUT PERATURAN KEPOLISIAN NOMOR 8 TAHUN 2021 - Fachtu Robbi Almalik (2022)
Termination of the investigation is the process of resolving criminal cases by the Indonesian National Police as law enforcement officers. The settlement of criminal cases is also often associated with a method that is currently emerging, namely restorative justice. However, the application of restorative justice needs to be perfected to achieve justice. The National Police has formulated the rules through the Chief of Police Circular Number SE/8/VII/2018 concerning the Application of Restorative Justice in the Settlement of Criminal Cases. The National Police also issued Police Regulation Number 8 of 2021 concerning the Handling of Crimes based on Restorative Justice. However, it is constrained by the Criminal Procedure Code which does not or has not regulated the termination of investigations based on restorative justice. This study aims to explain the mechanism of applying restorative justice in handling criminal acts at the investigation stage. It also outlines the factors that hinder the implementation of restorative justice in the police force. The research method used is a normative juridical method using a law approach. The data collection technique used is literature study. The conclusion obtained from the results of this study is that the application of restorative justice at the investigation stage has been regulated in Polri Regulation Number 8 of 2021. However, the National Police must improve the integrity and professionalism of its members in processing a criminal case so that the principles and objectives of this restorative justice can be realized , besides that, special rules are needed regarding the application of restorative justice in law enforcement in Indonesia.